PENGARUH MEDIA FLASHCARD TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 88 PALEMBANG - Aulia Windama, Miftah; Diah Budi Setyaningrum, Naomi; Puspita Sari Jaya, Melinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effect of flashcard media on students' interest in learning in class IV Indonesian language learning at SD Negeri 88 Palembang. The research uses quantitative methods in the form of a quasi experimental design, posttest only control group design. The research sample consisted of 62 students consisting of the experimental class and the control class. Data collection was carried out through observation and questionnaires, while data analysis used the normality test, homogeneity test and Independent Sample t-Test. The results showed that the average student interest in learning in the experimental class was 86.09, higher than the control class at 66.87. The results of the hypothesis test obtained a Sig value. (2-tailed) is 0.000 0.05, and based on 11.013 > 2.000 so that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that flashcard media has a significant effect on the learning interest of class IV students at SD Negeri 88 Palembang